Influência dos tipos de substratos na cinética mássica de produção da película celulósica do Kombucha - Batista, Maira Eloisa (2019)
Kombucha is an ancient drink discovered in China obtained by fermenting sweetened tea using a cellulosic film made of yeast and bacteria. The cellulosic film also known as SCOBY (English abbreviation, Symbiotic Culture of Bacteria and Yeasts, in Portuguese, Symbiotic Bacteria and Yeast Culture) is responsible for the fermentation giving rise to drink and a new film. Mainly made up of cellulose, yeast and bacteria. Its composition. In addition to beverage production, other alternatives are being developed for the use of cellulosic film. Some studies use this matrix for burn and dermal injury treatments, for the removal of metallic pollutants from aqueous solutions, such as biomaterial in nerve tissue engineering, poultry feeding and the use in the manufacture of vegan clothing. The substrates used in Kombucha fermentation are tea and sugar, the most used being black or green tea and crystal sugar. Due to the easy obtainment of the cellulosic film and its promising characteristics, this study aims to analyze the influence of substrate type (tea and sugar) on the kinetics of Kombucha cellulosic film production. The cellulosic film obtained by donation from a home producer in Curitiba was cultivated according to the literature, comparing the mass variation in different substrates. The obtained results are in agreement with the literature, being the honey a substrate that presented a bigger mass variation in comparison with the sugar. And in relation to tea, black tea got a better result compared to green tea.